2016
DOI: 10.1371/journal.pone.0155404
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Global Drivers of Ant Elevational Diversity

Abstract: Ant diversity shows a variety of patterns across elevational gradients, though the patterns and drivers have not been evaluated comprehensively. In this systematic review and reanalysis, we use published data on ant elevational diversity to detail the observed patterns and to test the predictions and interactions of four major diversity hypotheses: thermal energy, the mid-domain effect, area, and the elevational climate model. Of sixty-seven published datasets from the literature, only those with standardized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
100
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(117 citation statements)
references
References 67 publications
11
100
4
2
Order By: Relevance
“…Since the geographic area in Pampa is larger and the sampled sites were spatially further apart, there is indeed more heterogeneity of associated habitat conditions (e.g. soil types, vegetation physiognomies, plant richness; Streck et al, 2008;Ferreira et al, unpublished data) and thus a higher probability of finding a richer associated ant community in the Pampa. Ant fauna composition was also singular between these grassland regions (sharing only 43% of the total richness), and community structure based on dominant species also shifts regarding number of dominant species and their identity.…”
Section: Resultsmentioning
confidence: 99%
“…Since the geographic area in Pampa is larger and the sampled sites were spatially further apart, there is indeed more heterogeneity of associated habitat conditions (e.g. soil types, vegetation physiognomies, plant richness; Streck et al, 2008;Ferreira et al, unpublished data) and thus a higher probability of finding a richer associated ant community in the Pampa. Ant fauna composition was also singular between these grassland regions (sharing only 43% of the total richness), and community structure based on dominant species also shifts regarding number of dominant species and their identity.…”
Section: Resultsmentioning
confidence: 99%
“…Several taxa or functional groups have emerged as frequent subjects of diversity studies. Among insects, ants are commonly studied because they are a dominant component of ecosystems, they are diverse, and species-level identification is increasingly possible (Wilson and Hölldobler 2005, Szewczyk and McCain 2016, Tiede et al 2017). Here we report diversity patterns of leaf-litter ants in wet forests of the Middle American corridor.…”
Section: Introductionmentioning
confidence: 99%
“…A general approach has been to apply linear models, with richness as the response variable, and multiple predictor variables (temperature, precipitation, area, mid-domain effect). Szewczyk and McCain (2016) reviewed 20 studies of ant diversity on elevational gradients. The most common pattern was an asymmetrical mid-elevation peak in diversity, with the peak below the midpoint of the gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the butterfly fauna in this study is also lower than those recorded from higher mountains in Borneo such as Gunung Mulu National Park (276 species) [12] and Kinabalu National Park (625 species) [11], the species accumulation curves (Fig. 7) especially for elevations of 400 m and 800 m still exponentially increased, which suggested that there was an expectation to discover more species at each of these elevations with intensive samplings (more individuals sampled, more sampling time and larger size of study areas) [6]. In fact, more than half of the species found in this study were singletons and doubletons.…”
Section: Discussionmentioning
confidence: 89%